Pengembangan Gendhing Jawa Sebagai Media Pembelajaran Matematika - Sadieda, Lisanul Uswah; Hidayah, Ainisya Syifaul; Sunarto, Sabrilian Firdausa; Mufidah, Khurotul; Cahyaningtiyas, Yeni Tri (Jurnal PEKA (Pendidikan Matematika), 2025)
This research aims to develop a learning media in the form of Javanese songs that is valid and effective for statistics material. The research method used is R&D with the ADDIE model, which includes the phases of Analyze, Design, Development, Implementation, and Evaluation. Data were obtained through validation questionnaires, students’ response quisionnaire, and students’ learning tests. The research subjects were students of class VIII D at SMPN 2 Mojokerto. The validity test results from the validators showed good results, with an average score of 79.85% in the very valid category. Learning media using Javanese songs has also proven effective based on test results and students’ responses. The result of students’ learning outcomes show that the overall average score is 82.2 in the very good category. The results of the student response questionnaire indicate a very positive response category, with a percentage of 78.4%. Based on these results, it can be concluded that the learning media using the Javanese song "Lir-Ilir" integrated with statistics can serve as a means to improve the students’ learning outcomes and the classroom atmosphere.